A Map of Sea Surface Temperature in Rupat Strait Based on Satellite Image of Aqua-Modis - Rambe, Pahala Roy; Mubarak, Mubarak; Rifardi, Rifardi (Department of Marine Science, Faculty of Fisheries and Marine Universitas Riau, 2022)
The study aims to identify variations in the surface temperature of the water of Dumai, Riau province, using the AQUA-Modis satellite. Data analysis uses seadas and surfer software. In this study, the method used was the survey method. Ground check done was to establish the immediate value of ocean surface temperature. It also measures the quality of the water and gives documented observations of the waters. Parameters measured in this study are those of the quality of the water covering: brightness, temperature, acidity (pH), and salinity. The measured parameters for the quality of water in the Dumai waters were carried out at 3 stations that are thought to represent the parameters of the waters of the city of Dumai. The result of the measured parameters for the quality of the Dumai waters is known that for the value of the brightness of the dumai waters is between 7.5 and 16 cm, the water temperature is between 28-29 oC, the degree of acidity (pH) of water ranges between 6-7 and dumai water salinity (26-32‰). Based on studies that 2020 variations in surface temperature (SST) have a varying range of temperatures. Variations in surface temperature are marked by SST anomalies indicating that the value of negative anomalies indicates that an SST shift is marked by a drop in temperature.